2016
DOI: 10.1176/appi.ajp.2016.15081089
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of fMRI Studies of Disruptive Behavior Disorders

Abstract: The findings show that the most consistent dysfunction in youths with disruptive behavior disorder is in the rostro-dorsomedial, fronto-cingulate, and ventral-striatal regions that mediate reward-based decision making, which is typically compromised in the disorder. Youths with psychopathic traits, on the other hand, have dysfunctions associated with the ventromedial prefrontal cortex and limbic system, together with dorsal and fronto-striatal hyperfunctioning, which may reflect poor affect reactivity and empa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 103 publications
6
148
2
2
Order By: Relevance
“…Second, our discussion compares children reported here and adolescents reported elsewhere (Alegria et al, 2016; Raschle et al, 2015; Rogers and De Brito, 2016). Such cross-sectional comparisons should inform, but cannot replace, future longitudinal studies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Second, our discussion compares children reported here and adolescents reported elsewhere (Alegria et al, 2016; Raschle et al, 2015; Rogers and De Brito, 2016). Such cross-sectional comparisons should inform, but cannot replace, future longitudinal studies.…”
Section: Discussionmentioning
confidence: 84%
“…Alegria et al (2016) analyzed fMRI studies comparing youngsters (mean age 15 years) with or without disruptive behavior disorders. Participants with disorder had hypoactivation “in the rostro-dorsomedial, fronto-cingulate, and ventral striatal regions that mediate reward-based decision making”, very closely overlapping our Table 2 regions.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, the link here may not be causative but concurrent, given the role temporal poles play in regulating emotion processing in behavioral disorders. 37 We observed that some speech tasks and acoustic measures (such as timing metrics derived from the monologue, reading, DDK) were sensitive to speaker pathology, whereas others were disordered in both patients with bvFTD and healthy controls (e.g., hoarse voice, 75%; monopitch, 38%). If as suggested, speech tasks fit along a continuum of automaticity, 17 those tasks with increased cognitive load (e.g., unprepared monologue) should be more adversely affected by cognitive disorders where a motor impairment is not anticipated.…”
Section: -24mentioning
confidence: 84%
“…They confer considerable costs to society and are associated with relatively poor long-term prognoses. The meta-analytic review published in this issue (1) summarizes the findings of 24 functional magnetic resonance imaging studies of patients with these disorders and provides useful information regarding their pathophysiology. The authors conducted several meta-analyses of these studies: one omnibus analysis contrasting youth with disruptive behavior disorder/conduct problems across all tasks and then several sub-meta-analyses that examined group differences on tasks grouped according to whether they involved “hot” executive functioning, “cool” executive function or emotion processing.…”
mentioning
confidence: 99%